Effect of insulin on oxygen free radicals and oxidative phosphorylation in liver mitochondria of diabetic rats - Huang Qing; Shao Lan; Jiang Hong; Miao Zhen-Chuan; Shi Qing-De; Liu Shu-Sen (Acta Pharmacologica Sinica, 2016)
Aim: To observe the effects of insulin on liver mitochondrial respiratory function, activity of H+-ATPase, and superoxide anion free radicals production in diabetic rats. Methods: Rats were injected iv with alloxan 40 mg/kg to induce diabetes. The liver mitochondrial respiratory function was assayed by measurement of oxygen consumption using a Clark oxygen electrode. Superoxide anion production was assayed using chemiluminescence method. Activities of H+-ATPase were measured by luciferin-luciferase system and inorganic phosphorus's method. Results: Insulin 1 U/kg sc daily for 9 weeks improved oxidative phosphorylation, respiratory rate state 3 (P < 0.05), respiratory control ration (P < 0.01), and ADP:O ratio (P < 0.01), but there were no obvious effect on respiratory rate state 4 (P > 0.05). In the insulin group, synthesis activity of H+-ATPase was obviously increased (P < 0.05) and hydrolytic activity of H+-ATPase was remarkably decreased (P < 0.01), compared with the diabetes group. Insulin 1 U/kg for 9 weeks apparently decreased the production of O2.- (P < 0.01) in liver mitochondria of diabetic rats. Conclusion: Insulin can prevent the injury from superoxide anion in liver mitochondria, and improve the function of the liver mitochondria oxidative phosphorylation.